The impact of integration of Information Communication Technology (ICT) in the teaching of preschool children in Kiambu West Sub - County - Kang’ara, Hannah Wanjiku; Koech, Peter Kibet (Journal of Research in Humanities and Social Science, 2017)
Preschool learning has faced numerous challenges which have raised concerns among preschool education stakeholders. Preschool learners have registered and continued to register dismal grades in basic numeracy, language and creativity skills. Thus, the study examined the influence of teachers’ instructional practices on preschool learning in Kiambu West Sub-county, Kiambu County, Kenya. The objective of the study was to examine the impact of integration of Information Communication Technology (ICT) in the teaching of preschool children in Kiambu West Sub-County. This study based on instructional, learning and cognitive theories by Piaget. The study adopted mixed methods approach, concurrent triangulation design. Target population comprised of 80 head teachers, 187 preschool teachers and 240 parents’ representatives all totaling to 507. Using the Central Limit Theorem, a sample of 10 preschools and 86 respondents were selected. Stratified sampling was applied to create 5 strata based on number of zones. From each zone, 2 head teachers and 11 preschool teachers were selected using purposive sampling. 4 parents’ representatives were selected using simple random sampling. Questionnaires were used to collect data from preschool teachers, interview schedules were used to collect data from head teachers, whereas focus group discussion was used to collect data from parents’ representatives and observation checklists were used for collection of data from preschool learners. Piloting was conducted to establish validity, reliability, credibility and dependability. Validity was determined through expert judgement whereas reliability was determined using test retest technique. Reliability coefficient of r = 0.7, was realised using Pearson’s product moment correlation method, Credibility was ascertained by data triangulation through multiple analysts whereas dependability was established through detailed reportage of the data collection process. Qualitative data was analyzed thematically along the objectives and presented in narrative form whereas quantitative data was analyzed descriptively and inferentially using statistical package for social science (SPSS 23) and presented using statistical tables. The study established that preschool teachers in Kiambu West Sub-county are not prepared for the integration of ICT in the school curriculum and this ontinues to be a complex and challenging process in most of the county. These results however, affirm the fact that teachers’ instructional practices to adopt the use of ICT in preschool learning in the county is critical. Those schools reporting to have integrated information technology in their teaching reported enhanced syllabus coverage, mastery of content and learners’ academic performance in basic numeracy, language and creativity skills. The study concludes that teachers’ instructional practices need integration of ICT skills in order to enhance learning in preschools. It is also evident that most preschool teachers do not keep records of learners’ progress using computer generated hard copies confirming that there is poor utilization of ICT integration in preschools in the sub-county. The study recommends that teachers need attend ICT courses in order to equip themselves with the pre-requisite skills necessary to effectively infuse Information Communications Technology in the learning process.
Keywords: Integration; Information, communication Technology (ICT); Preschool